Hedonic Test of Instant Powdered Ginger Drink with Sugar and Sugar-Palm Sugar Combination - Jannah, Husnul; Badi'ah, Baiq Arriyadul; Amalia Rachman, Irna Ningsi; Desimal, Iwan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Stress, environmental pollution, radiation, and excessive food processing contribute to the production of free radicals, which are harmful to the body. Antioxidants play a role in preventing free radicals from damaging nucleotides. Ginger contains high levels of antioxidants, making it beneficial for overall health. However, ginger has a short shelf life, and its traditional preparation methods are less preferred by many people. Therefore, ginger is now available in the form of instant drink powders, which can be prepared like tea or coffee. This study is a descriptive study using the hedonic test method. Thirty students were selected as panelists. The panelists evaluated two types of ginger drinks made with different sweeteners: sugar and a combination of sugar and palm sugar (sugar-palm sugar). The parameters assessed in this study were color, aroma, taste, and sweetness level. The results of the hedonic test showed that the ginger drink sweetened with the sugar-palm sugar combination had the highest preference percentages across all parameters: color, aroma, taste, and sweetness level. For color, the